In vivo estimation of optic nerve sheath stiffness using noninvasive MRI measurements and finite element modeling. (October 2020) - Lee, Chanyoung; Rohr, Jesse; Sass, Austin; Sater, Stuart; Zahid, Arslan; Macias, Brandon; Stenger, Michael B.; Samuels, Brian C.; Martin, Bryn A.; Oshinski, John N.; Ethier, C. Ross
Abstract: The optic nerve sheath (ONS) is biomechanically important. It is acted on by tension due to ocular movements, and by fluid shifts and/or alterations in intracranial pressure (ICP) in human disease, specifically in pathologies leading to intracranial hypertension. It has also been hypothesized that the ONS is acted on by altered ICP in astronauts exposed chronically to microgravity. However, a non-invasive method to quantify ONS biomechanical properties is not presently available; knowledge of such properties is desirable to allow characterization of the biomechanical forces exerted on the optic nerve head and other ocular structures due to the ONS. Thus, the primary objective of this study was to characterize the biomechanical properties (stiffness) of the human ONS in vivo as a necessary step towards investigating the role of ICP in various conditions, including Spaceflight Associated Neuro-ocular Syndrome (SANS). We acquired non-invasive magnetic resonance imaging (MRI) scans of ostensibly healthy subjects (n = 18, age = 30.4 ± 11.6 [mean ± SD] years) during supine and 15-degree head-down-tilt (HDT) postures, and extracted ONS contours from these scans. We then used finite element modeling to quantify ONS expansion due to postural changes and an inverse approach to estimate ONS stiffness. Using this non-invasive procedure, we estimated an in vivo ONS stiffness of 39.2 ± 21.9 kPa (mean ± SD), although a small subset of individuals had very stiff ONS that precluded accurate estimates of their stiffness values. ONS stiffness was not correlated with age and was higher in males than females.